Hubungan Dukungan Ayah dengan Kelengkapan Imunisasi Dasar Lengkap pada Bayi 0 – 1 Tahun di UPT Puskesmas Tamban Baru - Rodianor Rodianor; Aloysia Ispriantari (Lembaga Pengembangan Kinerja Dosen, 2026)
Immunization is a preventive measure used to protect against Tuberculosis, Diphtheria, Pertussis, Polio, Hepatitis B, and Measles. Immunization administration must be continuous, comprehensive, and conducted according to standards to provide effective health protection. The objective of this study was to determine the correlation between paternal support and the immunization status of children aged 0 to 1 year in the Tamban Baru Community hEalth Center area, Kapuas Regency. This study used a cross-sectional correlation design. The independent variable was paternal support, and the dependent variable was immunization status. The sample was selected using total sampling technique, consisting of 50 respondents. Data collection was performed using a questionnaire. The results showed a significant correlation between paternal support and the immunization status of children aged 0 to 1 year, indicated by p = 0.000017 < 0.005; thus, the null hypothesis (H0) was rejected and the alternative hypothesis (H1) accepted. This means that there is a correlation between paternal support and the immunization status of children aged 0 to 1 year. It is recommended that that cross-sector collaboration and Community Health Center authorities enhance efforts so that every immunization officer provides health education, such as counseling about immunization, and that family involvement in spreading immunization programs is increased to achieve targeted coverage through cooperation with health professionals.